2015
DOI: 10.1038/onc.2015.340
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR enhances ER signaling and confers tamoxifen resistance in breast cancer

Abstract: Tamoxifen, an estrogen receptor (ER) antagonist, is the mainstay treatment of breast cancer and the development of resistance represents a major obstacle for a cure. Although lncRNAs such as HOTAIR have been implicated in breast tumorigenesis, their roles in chemotherapy resistance remain largely unknown. In this study, we report that HOTAIR is up-regulated in tamoxifen-resistant breast cancer tissues compared to their primary counterparts. Mechanistically, HOTAIR is a direct target of ER-mediated transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
274
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(288 citation statements)
references
References 36 publications
12
274
1
1
Order By: Relevance
“…The authors concluded that HOTAIR increases ligandindependent ERα transcription. This observation is concordant with a report of increased HOTAIR immunstaining in tamoxifen-resistant human breast tumors (Xue et al 2016b). …”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancerssupporting
confidence: 82%
See 2 more Smart Citations
“…The authors concluded that HOTAIR increases ligandindependent ERα transcription. This observation is concordant with a report of increased HOTAIR immunstaining in tamoxifen-resistant human breast tumors (Xue et al 2016b). …”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancerssupporting
confidence: 82%
“…HOTAIR is upregulated by HIF-1α, histone methylase MLL1, and coactivator p300 (Bhan, et al 2017). HOTAIR was reported to be induced by E 2 in MCF-7 BCa cells (Bhan, et al 2013), but others reported that E 2 -ERα directly that repressed HOTAIR in MCF-7 cells by binding to a genomic site 14.5 kB upstream of HOTAIR (Xue, et al 2016b). HOTAIR is downregulated by miR-141 (Chiyomaru, et al 2014) and is directly targeted by miR-34a in PCa cells (Chiyomaru, et al 2013).…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, loss of BRCA1 or upregulation of HOTAIR results in the reprogramming of the genome-wide PRC2-binding pattern in breast epithelial cells, leading to the altered methylation signature found in aggressive breast cancer cells [178]. Recently HOTAIR has been shown to be upregulated in tamoxifen-resistant breast cancer tissues compared with their primary counterparts [179]. This facilitates the ligand-independent activation of ER, which contributes to tamoxifen resistance [179].…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%
“…6 In recent years, several studies have implicated lncRNAs in various malignancies. For instance, HOTAIR has been reported as being overexpressed in breast cancer and 7,8 CRC. [9][10][11] CCAT2 was identified as a novel lncRNA overexpressed in CRC which promotes metastasis and chromosomal instability.…”
Section: Introductionmentioning
confidence: 99%